Found this function here
http://jsfromhell.com/string/expand-exponential
String.prototype.expandExponential = function(){
return this.replace(/^([+-])?(\d+).?(\d*)[eE]([-+]?\d+)$/, function(x, s, n, f, c){
var l = +c < 0, i = n.length + +c, x = (l ? n : f).length,
c = ((c = Math.abs(c)) >= x ? c - x + l : 0),
z = (new Array(c + 1)).join("0"), r = n + f;
return (s || "") + (l ? r = z + r : r += z).substr(0, i += l ? z.length : 0) + (i < r.length ? "." + r.substr(i) : "");
});
};
I sort of get the replace part, but I'm lost when I see the function(x,s,n,f,c) part. What am I missing?
Can someone help me break this down into more understandable components?
See this page
Basically, x
is the matched substring. s
corresponds to the part that was matched by the first pair of parentheses (([+-])
), n
corresponds to the part matched by the second parentheses ((\d+)
), and so on.
The matched string is replaced by the value returned by this function.